Equilibrium and Kinetic Studies of Crude Oil Sorption on Unmodified and Modified Napier Grass - Obi, Amalachukwu Ifeyinwa; Ajiwe, Vincent Ishmael; Okonkwo, Chinwe Priscilla (Makara Journal of Science, 2023)
Nowadays, natural organic adsorbents are widely used to clean up oil from spills owing to their effectiveness, affordability, and biodegradability. In this study, Napier grass, a widely available agricultural material, was used to remove crude oil from aqueous media. The Napier grass was modified via a mild acetylation process to improve its hydrophobicity. The modification increased the Brunauer–Emmett–Teller surface area of the grass from 180.07 to 271.13 m2/g. Fourier-transform infrared analysis revealed that the modification endowed the originally hydrophilic Napier grass with hydrophobicity. The oil sorption processes were based on monolayer physisorption and controlled by film diffusion. The oil sorption capacities of the unmodified and modified Napier grass under various adsorption conditions (adsorbent dose, initial crude oil concentration, and contact time) were significantly different. The equilibrium oil sorption capacities of the unmodified and modified grass were 7070 and 9057 mg/g, respectively, reflecting the improvement of oil sorption capacity by the modification process. These results indicate that the modification process significantly improved the crude oil adsorption ability of Napier grass. Thus, acetylated Napier grass is an effective, readily available oil sorbent with application potential for the cleanup of crude oil spills.